The Impact of Financial Risk, Liquidity Risk, and Operational Risk on Islamic Rural Bank Performance - Nita Gustiyana; Sania Nuraziza (Department of Islamic Banking, 2025)
Purpose – This study aims to analyze the effect of the application of financing risk management, liquidity, and operations on the performance of Sharia Rural Banks (SRB) in Bandar Lampung from 2014 to 2024. Methodology – Type of data in this study using quantitative methods in the form of secondary data from the financial statements of the Sharia Rural Banks contained in the entire city of Bandar Lampung to obtain data from Bandar Lampung Islamic Bank PT. BPRS Bandar Lampung and PT BPRS Mitra Agro Usaha. The nature of explanatory research. The population in this study comprises all Sharia Rural Banks in Lampung from 2014 to 2024. The sampling method is saturated sampling. The method of data analysis used in this study is multiple linear regression analysis, utilizing SPSS software. Findings – The results showed that simultaneously variable Financing Risk, Liquidity Risk, and Operational Risk significantly affect the profitability of Sharia Rural Banks in Bandar Lampung. Implications – SRB management can use the research findings to identify areas of weakness in the application of financing, liquidity, and operational risk management. This will help them devise more effective risk mitigation strategies. Originality – Sharia Rural Banks, in achieving their profitability, will undoubtedly face various risks; risk management is a crucial filter in identifying, measuring, monitoring, and controlling the course of the bank's business activities. Risks that occur will cause losses to the bank if not detected and managed correctly, so the bank must implement effective risk management.